Two ecological gradients drive phenotypic differentiation of a cave fish over a few hundred metres. (18th February 2022) - Riesch, Rüdiger; Curtis, Amy; Jourdan, Jonas; Schlupp, Ingo; Arias-Rodriguez, Lenin; Plath, Martin
Abstract: Ecological gradients can drive adaptive phenotypic diversification, but the extent of local adaptation depends on the strength, temporal stability and spatial dimensions of selective forces at play. We examined diversification in morphology and life histories of a live-bearing fish ( Poecilia mexicana ) that has adapted to two concomitant gradients: differential light regimes and toxicity levels in and around a hydrogen sulphide-rich cave. Even though typical ranging distances of P. mexicana exceed the spatial dimensions of both gradients (few hundred metres), clines in head size, body depth, male and female lean mass, offspring size, fecundity and maternal provisioning strategies tracked both gradients. Comparison of two life-history samplings from 2007/2008 and 2014 revealed remarkable temporal stability, even though some degree of temporal variation was seen in fat content and investment into reproduction. Our study demonstrates how patterns of phenotypic gradient evolution can emerge when spatially and temporally stable, strong selection forces alter selective landscapes, resulting in alternate fitness optima of different locally adapted genotypes and impeding individuals' movement even at a spatial scale far below the species' potential lifetime ranging distance. This is further evidence for the role of active colonization and gradual adaptation to cave environments in the evolution of some cave organisms.